Can sag and ball mills operate on weak network conditions? the case study and the solution - Reinhold A. Errath (Instituto de Ingenieros de Minas del Peru, 2003)
"The paper describes the problem related with contradiction to the development of sag mills, which one are becoming bigger in size almost every year. In this sense, the concentrator plants are being built more and more in remote areas where the power supply and network conditions are not necessarily covering the needs for the operation of such plants. It also illustrates the permissible tolerances in terms of commutation of the powerelectronics, based on already realized installations. Finally the paper gave an overview about the technical impact of a strong versus weak networks."